(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
Fingerprint powders have been used for decades as a robust technique for the developing latent fingerprints. However, inhaling traditional powers can pose health hazards for the person using it and those around them. This research aimed to develop a safer and cost-effective method for visualizing latent fingerprints on non-porous surfaces. The study used non-toxic plant-origin powders extracted from Clitoria ternatea and Curcuma longa. The powders were manufactured using a simple methodology and were evaluated for their effectiveness in developing fingerprints on different surfaces. The results showed that Clitoria ternatea powder can develop latent fingerprints on plastic, wooden laminate, glass, and steel surfaces, while Curcuma longa powder was effective on glass and laminate surfaces. The development process revealed clear ridge patterns that can be compared to known fingerprints for identification purposes. The use of natural sources reduces the toxicity of the powders, making them safer to use compared to traditional powders. This study presented promising results in developing latent fingerprints.